Do the Fertility Drugs Increase the Risk of Cancer? A Review Study - Momenimovahed, Zohre; Taheri, Safoura; Tiznobaik, Azita; Salehiniya, Hamid (Frontiers in Endocrinology, 2019)
Aim: All over the world, many couples cannot conceive a child and have problems with pregnancy. Ovulation-inducing drugs are among the most important drugs used for the treatment of infertility. In recent years, there have been many debates about the relationship between fertility medication and cancer. Due to the lack of comprehensive study of this matter, and as understanding the relationship between the use of fertility drugs and cancer is of importance, the present study was conducted to investigate the relationship between infertility drugs and cancer in women. Materials and Methods: To determine the relationship between infertility treatment and cancer, a comprehensive search was carried out in databases such as; Medline, Web of Science Core Collection, and Scopus using keywords words; “infertility,” “ovulation induction,” “cancer,” “infertility treatment,” “ART,” “tumor,” “controlled ovarian stimulation,” “fertility agents,” and “neoplasms.” Full-text, English language, and original articles were included in this study. Results: In total, 81 articles were entered into the study. The relationship between fertility medications and breast, ovary, endometrial, uterus, colon, thyroid, skin, cervical, and non-Hodgkin's lymphoma cancers were studied. Although the relationship between fertility medications and cancer is theoretically justifiable, most studies have shown that risk of cancer will not increase after fertility treatment. Conclusion: The results of this study did not show that fertility medications increase the risk of cancer among users. In summary, the relationship between infertility treatment and cancer incidence remains an open question.